2003
DOI: 10.1002/ijc.11340
|View full text |Cite
|
Sign up to set email alerts
|

Mast cell inhibitor cromolyn increases blood clotting and hypoxia in murine breast cancer

Abstract: Human breast cancer is extensively infiltrated by mast cells that contain powerful anticoagulants such as heparin, tryptase and chymase. To determine if human breast cancer is associated with mast cell activation, we measured the levels of mast cell tryptase (an indicator of mast cell activation) in the blood of 20 women with varying stages of breast cancer. The mean level of tryptase in women with breast cancer (10.3 ؎ 4.2 g/L) was significantly higher than in 50 normal healthy women without breast cancer (3.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 36 publications
(49 reference statements)
1
45
0
1
Order By: Relevance
“…Increased MCT in level in sera of patients with breast cancer has been shown, previously (Samoszuk and Corwin, 2003), One study showed their importance as a diagnostic and prognostic marker for distinguishing pancreatic cancer from benign tumors in the same location (Strouch et al, 2010). According to the previous reports; we hypothesized that mast cell activation could be a useful parameter for evaluating OSCC patients.…”
Section: Introductionmentioning
confidence: 77%
See 3 more Smart Citations
“…Increased MCT in level in sera of patients with breast cancer has been shown, previously (Samoszuk and Corwin, 2003), One study showed their importance as a diagnostic and prognostic marker for distinguishing pancreatic cancer from benign tumors in the same location (Strouch et al, 2010). According to the previous reports; we hypothesized that mast cell activation could be a useful parameter for evaluating OSCC patients.…”
Section: Introductionmentioning
confidence: 77%
“…MCT level in biologic fluids is used as an indicator of number and activation of mast cells (Hogan and Schwartz, 1997). This level has been determined in breast and pancreatic cancer (Samoszuk and Corwin, 2003;Strouch et al, 2010). Strouch et al have stated that mast cell accumulation in the tumoral tissue may be reflected in the serum and the serum level of tryptase may be a useful marker to distinguish malignant from benign tumors (Strouch et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been demonstrated previously that inflammatory cells play an important role in both mammary gland development [11,12] and mammary tumor progression [13][14][15][16]. However, no previous work has attempted to elucidate the specific role of mast cells in mammary gland development.…”
Section: Bodymentioning
confidence: 99%